Peran Guru PAI sebagai Role Model dalam Pembentukan Akhlak Peserta Didik di Era Digital - M.Luthfi Al-Fatih Al-Fatih; Martin Kustati; Bashori Bashori (Educational Research Center, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers as role models in shaping students' morals in the digital era. The digital era brings new challenges in character education, where students are exposed to various content that is not always in accordance with Islamic values. This study uses a qualitative approach with case study methods in three junior high schools in Padang City. Data was collected through observation, in-depth interviews with PAI teachers, students, and principals, and document analysis. The results of the study show that PAI teachers play a role model through four main dimensions: wise digital behavior examples, integration of moral values in technology-based learning, guidance on the ethical use of social media, and consistency between words and deeds in digital and real contexts. The findings revealed that the effectiveness of PAI teachers' exemplary skills is highly dependent on teachers' digital literacy skills, personal credibility, and the intensity of interaction with students. This study recommends the need to improve the digital competence of PAI teachers that is integrated with Islamic moral values, as well as the development of a moral development model that is adaptive to the dynamics of the digital era.